High-precision measurements of curling stone dynamics: Curl distance by digital image analysis - Hattori, K.; Tokumoto, M.; Kashiwazaki, K.; Maeno, N. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2016)
Curl distance is one of the most important factors for a curler to control carefully and seriously in a game of curling. Curl distance was measured with high-precision digital image analysis in order to obtain its precise relationship with the number of rotations. Motion of the curling stone was recorded in sequential images with two cameras located on the ceiling. Calibrations to remove lens aberration and to connect the imaging areas of the two cameras were done prior to the experiment. The initial direction of the stone in each delivery was calculated as a reference line using the positions of the stone derived from the sequential images. Then, the curl distance was measured as a distance from the stop position of the stone perpendicular to the reference line, which was corrected as to convert the translation of the stone equivalent to the distance between the hog line and the tee line, 93?ft (28.3?m). It was found that the curl distance decreases as the number of rotations increases in the range of measurements made in the experiment. The decrease rate was 0.047-0.064?m per rotation and varied slightly with ice sheet conditions.